PASSENGER CAR SPEED ASSESSMENT RELATIONSHIP TO THE NOISE CAUSED - Syaiful, Syaiful; Andana, Rendy (Universitas Ibn Khaldun Bogor, 2021)
Noise is defined as a human unwanted sound. The main sources of noise on toll roads are heavy vehicles and light vehicles. Noise pollution is often interpreted as unwanted sound or wrong sound at the wrong time. as heavy industry grows, traffic crowds, transportation facilities, and excessive use of audio technology. In addition there is generally noise strongly related to annoyance. Noise is everywhere and disturbance is one of the most common reactions to noise.. Speed is the size of a vector that shows how fast objects move. This research aims to find out the level of traffic noise and its distribution in front of SDN Cimahpar 01. The research method uses multiple linear analysis with the SPSS program by entering traffic data, vehicle speed and noise generated. The results were obtained that in SDN Cimahpar 01 area with the highest linear regression value between speed and noise that arises is 98% with linear regression equation y=52,390+0.298x1+0.229x2+0.245x3+0.205x4. Based on the similarity, the noise level value generated by the speed of the vehicle is 52.39 dBA with the provision of no increase or decrease in vehicle speed, this noise level is very strong because above the raw value of the activity noise level set by the Decree of the Minister of Environment No. 48 of 1996 which is 80 dBA.